The mechanisms behind consumer behavior changes of sugar-sweetened beverage tax and policy implications - Liu, Lu; Chen, Kevin Z. (China Academic Journals Electronic Publishing House Co., 2024)
Sugar-sweetened beverage（SSB）tax could impact consumer behaviors through price and non-price mechanisms. Price mechanism affects SSB consumption through price changes, relative price changes, or expected price changes in the future respectively. Non-price mechanism changes SSB consumption by reminding consumers of the adverse health impact of SSB consumption, guiding individual consumption through social norms, utilizing the correlation of SSB consumption among peers, and through consumers′ psychological responses respectively. In comparison with the price mechanism of SSB tax, the non-price mechanism originates from multiple factors and may function far before the formal implementation of the tax, which implies that non-price mechanism could be more effective in reducing SSB demand than price mechanism. Therefore, utilizing media publicity, exerting social normative effects, and promoting tax system innovation are proposed to effectively reduce SSB demand.